Causal Mechanisms in Corporate Social Responsibility (CSR) Management: A Meta‐Synthesis of Micro‐CSR Research - Remmer, Stefanie; Gilbert, Dirk Ulrich (Journal of Management Studies, 2026)
Abstract Much psychologically oriented micro‐CSR research emphasizes intra ‐individual processes, leading to a relative omission of the role of interactions among individuals in managing CSR. This limitation hinders the potential of such micro‐CSR research to explain CSR as an organizational‐level outcome. We adopt a meta‐synthesis methodology to extract insights on inter ‐individual processes in CSR management from existing literature that examines CSR's microfoundations beyond a purely psychological perspective. By incorporating a causal mechanism approach into our meta‐synthesis, we develop a theoretical framework comprising three causal mechanisms that elucidate how individual behaviours and interactions of differing sets of dominant actor types (including change agents, supporters, opportunists, resisters and top and senior management) foster substantive or incremental progress in CSR or its obstruction within firms. Our findings establish a foundation for further research into individual‐level and temporal dynamics in CSR management, and the conditions under which firms are more likely to implement impactful CSR initiatives.